1994
DOI: 10.1136/gut.35.4.483
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus acidophilus LA 1 binds to cultured human intestinal cell lines and inhibits cell attachment and cell invasion by enterovirulent bacteria.

Abstract: Four human Lactobacillus acidophilus strains were tested for their ability to adhere onto human enterocyte like Caco-2 cells in culture. The LA 1 strain exhibited a high calcium independent adhesive property. This adhesion onto Caco-2 cells required a proteinaceous adhesion promoting factor, which was present in the spent bacterial broth culture supernatant. LA 1 strain also strongly bound to the mucus secreted by the homogeneous cultured human goblet cell line HT29-MTX. The inhibitory effect of LA 1 organisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
380
4
17

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 644 publications
(425 citation statements)
references
References 34 publications
17
380
4
17
Order By: Relevance
“…Therefore, it can be hypothesized that competition for the binding site is a major mechanism through which lactic acid bacteria antagonize S. aureus and P. aeruginosa. Lactic acid bacteria counteract the adhesive and invasive function of pathogenic bacteria by causing a nonspecific steric hindrance action on the pathogenic receptors (Bernet et al, 1993;Bernet et al, 1994), and by producing inhibitory metabolites. Coconnier-Polter et al (2005) have previously reported that the CFS of L. acidophilus could potentially decrease the intracellular ATP content in S. enterica SL1344.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be hypothesized that competition for the binding site is a major mechanism through which lactic acid bacteria antagonize S. aureus and P. aeruginosa. Lactic acid bacteria counteract the adhesive and invasive function of pathogenic bacteria by causing a nonspecific steric hindrance action on the pathogenic receptors (Bernet et al, 1993;Bernet et al, 1994), and by producing inhibitory metabolites. Coconnier-Polter et al (2005) have previously reported that the CFS of L. acidophilus could potentially decrease the intracellular ATP content in S. enterica SL1344.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated that lactic acid bacteria stimulate macrophage phagocytosis of viable Salmonella (Hatcher & Lambrecht, 1993), enhance IgA production in intestinal secretions (Perdigon et al, 1990), produce an antimicrobial substance (Shahani & Ayebo, 1980;Silvia et al, 1987), inhibit cell attachment and cell invasion by enterovirulent bacteria (Bernet et al, 1994), and decrease intestinal permeability for macromolecules during rotavirus induced diarrhoea (Isolauri et al, 1993).…”
Section: Lactic Acid Bacteria H Hove Et Almentioning
confidence: 99%
“…Lactobacilli are prominent members of the microbiota. Lactobacillus johnsonii (La1), formerly known as L. acidophilus (Finegold et al, 1983) is a Lactobacillus strain of human origin that has been selected because of its ability to adhere to human intestinal mucosa (Bernet et al, 1994). Human in vivo studies have proven that La1 supports the physiological function of the gastrointestinal tract (GIT) and stimulates the immune defense (Pfeiffer & Rosat, 1999).…”
Section: Introductionmentioning
confidence: 99%